2020
DOI: 10.35118/apjmbb.2020.028.4.04
|View full text |Cite
|
Sign up to set email alerts
|

Effect of storage and frying times on stability of acrylamide and 5-hydroxymethylfurfural in fresh and frozen curry puff skins

Abstract: Acrylamide and 5-hydroxymethylfurfural (HMF) are potential compounds that are known to be neurotoxic, mutagenic, and carcinogenic when exposed to humans. These components are formed during Maillard reaction at which sugar is reduced and specific amino acids react at high temperature, and thus producing brown colour and flavour in food. Therefore, the aim of this study was to observe the formation level of acrylamide and HMF in fresh and frozen curry puff skins. This study investigated the effects of frozen sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Ridzala et al 49 revealed that −18 °C reduced the HMF by 50% after 28 days. Blanching with boiling water for 1 min might also form HMF at very low levels due to heating with the level of Abbreviations: FBAC = fresh sample treated with blanching (boiled water at 96 °C ± 4 °C for 1 min) + 2% ascorbic acid / 2% citric acid before freezing; PBAC = pre-frozen sample treated with blanching (boiled water at 96 °C ± 4 °C for 1 min) + 2% ascorbic acid / 2% citric acid before freezing; FB = fresh sample treated with blanching only (boiled water at 96 °C ± 4 °C for 1 min) before freezing; PB = pre-frozen sample treated with blanching only (boiled water at 96 °C ± 4 °C for 1 min) before freezing; FN = fresh sample with no blanching and no ascorbic acid / citric acid before freezing; PN = refrozen sample with no blanching and no ascorbic acid / citric acid before freezing.…”
Section: Resultsmentioning
confidence: 99%
“…Ridzala et al 49 revealed that −18 °C reduced the HMF by 50% after 28 days. Blanching with boiling water for 1 min might also form HMF at very low levels due to heating with the level of Abbreviations: FBAC = fresh sample treated with blanching (boiled water at 96 °C ± 4 °C for 1 min) + 2% ascorbic acid / 2% citric acid before freezing; PBAC = pre-frozen sample treated with blanching (boiled water at 96 °C ± 4 °C for 1 min) + 2% ascorbic acid / 2% citric acid before freezing; FB = fresh sample treated with blanching only (boiled water at 96 °C ± 4 °C for 1 min) before freezing; PB = pre-frozen sample treated with blanching only (boiled water at 96 °C ± 4 °C for 1 min) before freezing; FN = fresh sample with no blanching and no ascorbic acid / citric acid before freezing; PN = refrozen sample with no blanching and no ascorbic acid / citric acid before freezing.…”
Section: Resultsmentioning
confidence: 99%
“…After 3 minutes of frying at 190 o C compared to 9 minutes at 150 o C, the amount of acrylamide was around 40 times higher. With longer frying times, acrylamide production also decreased (Ridzala et al, 2020). The amount of acrylamide generated depends on the dietary matrix, temperature influences the quantity of acrylamide formed as the production typically increases beyond 120°C (Yang et al, 2016).…”
Section: I)time and Temperature During Fryingmentioning
confidence: 99%